Experiences of obstetric fistula patients at Mercy Women’s Catholic hospital in central region - (:unkn) unknown (University of Cape Coast, 2024)
Obstetric fistula is an important public health issue that disproportionately affects women in Ghana. The study explored the lived experiences of obstetric fistula patients at Mercy Women‘s Catholic Hospital at Mankessim in the Central Region. The phenomenological research design with homogenous purposive sampling technique was used to select 20 participants. An in-depth interview data collection method was used and thematic analysis was employed using NVivo 12.0. The results revealed that participants experienced complex physical and hormonal changes, including genital sores, frequent abdominal pain, menstrual variations, and foot drop. Affected women also faced significant economic challenges, such as difficulty in paying for high hospital bills, inability to pursue gainful employment, job loss, and reduced income. To cope with these burdens, women living with obstetric fistula engaged in various strategies, including avoidance of long-distance walking, self-restriction, keeping their condition secret, and maintaining high standards of hygiene. The study concluded that women suffering from obstetric fistula endure multifaceted physical, economic, and psychosocial challenges, and the study recommends that the Government of Ghana should enhance healthcare access, increase public awareness, and offer rehabilitation services to improve the quality of life for women with obstetric.
xiii,195p:,ill
Keywords: Coping mechanism Economic related Experiences Obstetric fistula Physical and hormonal changes Psychosocial